Pengembangan Evaluasi Sumatif Berbasis Quizizz Materi Perubahan Wujud Benda di Kelas III Sekolah Dasar - Suryadi, Dwi; Arsil, Arsil; Zahyuni, Violita (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to determine the development procedure, level of validity, and level of product practicality for a Quiziz-based summative evaluation of material on changes in the shape of objects in class III of SD Negeri 55/1 Sridadi, Muara Bulian District, Batang Hari Regency. This research is research and development (development research) which uses two models in development research, namely 4D and ADDIE. This research concludes that the development of a Quizizz-based summative evaluation on material changing the shape of objects in class III of SD Negeri 55/I Sridadi has had a positive influence on both students and teachers. The Quizizz application can be an effective alternative for summative evaluation in elementary schools, especially at SDN 55/I Sridadi.